Identification of QTLs Containing Resistance Genes for Sclerotinia Stem Rot in Brassica napus Using Comparative Transcriptomic Studies - Qasim, Muhammad Uzair; Zhao, Qing; Shahid, Muhammad; Samad, Rana Abdul; Ahmar, Sunny; Wu, Jian; Fan, Chuchuan; Zhou, Yongming (Frontiers in Plant Science, 2020)
Sclerotinia stem rot (SSR) is a major disease in Brassica napus that causes yield losses of 10-20% and reaching 80% in severely infected fields. SSR not only causes yield reduction but also causes low oil quality by reducing fatty acid content. There is a need to identify resistant genetic sources with functional significance for the breeding of SSR-resistant cultivars. In this study, we identified 17 QTLs involved in SSR resistance in three different seasons using SNP markers and disease lesion development after artificial inoculation. There were no common QTLs in all three years, but there were three QTLs that appeared in two seasons covering all seasons with a shared QTL. The QTLs identified in the two years were SRA9a, SRC2a and SRC3a with phenotypic effect variances of 14.75% and 11.57% for SRA9a, 7.49% and 10.38% for SRC3a and 7.73% and 6.81% for SRC2a in their two years, respectively. The flowering time was also found to have a negative correlation with disease resistance, i.e., early-maturing lines were more susceptible to disease. The plant width (diameter) has shown a notably weak effect on disease development, causing researchers to ignore its effect. Given that flowering time is an important factor in disease resistance, we used comparative RNA-seq analysis of resistant and susceptible lines with consistent performance in three years with almost the same flowering time to identify the resistance genes directly involved in resistance within the QTL regions. Overall, there were more genes differentially expressed in resistant lines than in susceptible lines compared to their mock-inoculated lines, demonstrating their tendency to cope with disease. We identified 36 putative candidate genes from the resistant lines that were upregulated in resistant lines compared to resistant mock and susceptible lines that might be involved in resistance to SSR.